PERAN BANK SAMPAH TRI ALAM LESTARI DALAM PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN KUALITAS LINGKUNGAN - Affan Rizqillah Aulia; Tantan Hermansah (Jurnal Kommunity Online, 2022)
Abstract This research aims to explain the role and analyze the results of community empowerment through activities at the Tri Alam Lestari Waste Bank to improve environmental quality. This study uses a qualitative approach and purposive techniques in the selection of research informants. Data mining is done by means of observation, interviews, documentation and literature study. Using data analysis techniques proposed by Miles and Huberman, and data validity techniques using source triangulation. Based on research that has been carried out, the Tri Alam Lestari Waste Bank carries out the roles of Facilitative Roles, Educational Roles, Representational Roles and Technical Roles in community empowerment to improve environmental quality through activities in the waste bank. The results of the empowerment in this study indicate that the Tri Alam Lestari Waste Bank through the activities carried out can improve the quality of the environment, as seen from the increasingly clean and well-maintained environment and the people who are starting to become aware of protecting the surrounding environment.